Effectiveness of using Social Media to Raise Public Awareness during the COVID-19 Pandemic in Bangladesh (Global Journal of Human-Social Science, 2022)
Social media has been one of the most effective and influential forms of communication in providing day-to-day information during the COVID-19 pandemic The study demonstrates the effectiveness of social media platforms in raising public awareness in Bangladesh during the pandemic The study employs a quantitative method based on 833 Male 86 8 Female 13 2 valid responses from citizens of Bangladesh disseminated through an online questionnaire using social media channels Datasets were analyzed through statistical tools using Microsoft Excel and SPSS version 26 IBM Corp e g Frequency and Percentage Descriptive Statistics Principal Component Analysis PCA and Pearson s Correlation Matrix PCM Based on the findings Facebook 78 3 has been the most used social media platform during the pandemic in Bangladesh However statistics of the majority 44 1 indicate that only 37 of awareness 37 related posts on social media attract their attention The study indicates that social media has been essential in raising awareness amongst the majority of the citizens Mean 4 14 providing updates Mean 4 05 and accurate Mean 4 05 information to the masses Awareness through social media has resulted in citizens becoming highly aware of the necessity of washing hands maintaining social distance wearing masks and learning about vaccination authenticating the influence of changing citizens behavior Although there is a risk of spreading incorrect information via social media its effective utilization can significantly raise public awareness during a global crisis such as COVID-19 influencing citizen behavior
Keywords: social media use; public awareness; citizens; covid-19 pandemic; bangladesh